Sepsis-Associated Coagulopathy Predicts Hospital Mortality in Critically Ill Patients With Postoperative Sepsis - Ren, Chao; Li, Yu-xuan; Xia, De-meng; Zhao, Peng-yue; Zhu, Sheng-yu; Zheng, Li-yu; Liang, Li-ping; Yao, Ren-qi; Du, Xiao-hui (Frontiers in Medicine, 2022)
Background: The incidence of coagulopathy was commonly seen among septic patients, which was responsible for poor outcomes. In the current study, we aim to determine whether the presence of sepsis-associated coagulopathy (SAC) predicts clinical outcomes among critically ill patients with postoperative sepsis. Methods: We conducted a single-center retrospective cohort study by including sepsis patients admitted to surgical ICU of Chinese PLA General Hospital from January 1, 2014 to December 31, 2018. Baseline characteristics and clinical outcomes were compared with respect to the presence of SAC. Kaplan-Meier analysis was applied to calculate survival rate, and Log-rank test was carried out to compare the differences between two groups. Furthermore, multivariable Cox, logistic and linear regression analysis were performed to assess the relationship between SAC and clinical outcomes, including hospital mortality, development of septic shock and hospital length of stay (LOS), respectively. Additionally, both sensitivity and subgroup analyses were performed to further testify the robustness of our findings. Results: A total of 175 patients were finally included in the current study. Among all included patients, 41.1% (72/175) ICU patients were identified as having SAC. In-hospital morality rates were significantly higher in SAC group when compared to that of the No SAC group (37.5% vs. 11.7%; P < 0.001). By performing univariable and multivariable regression analyses, presence of SAC was demonstrated to significantly correlate with increased in-hospital mortality for septic patients in surgical ICU (Hazard ratio [HR], 3.75; 95% Confidence interval [CI], 1.90-7.40; P < 0.001). Meanwhile, complication of SAC was found to be the independent predictor of the development of septic shock (Odds ratio [OR], 4.11; 95% CI, 1.81-9.32; P = 0.001), whereas it was not significantly associated with prolonged hospital LOS (OR, 0.97; 95% CI, 0.83-1.14; P = 0.743). Conclusion: The presence of SAC was significantly associated with increased risk of in-hospital death and septic shock among postoperative sepsis patients admitted to ICU. Moreover, there was no statistical difference of hospital LOS between SAC and no SAC groups.